Semantic Web-based Video Streaming Application - Ahmad, Ashraf M. A.; Abou El-Seoud, Samir (International Journal of Emerging Technologies in Learning (iJET), 2008)
An efficient moving object extraction algorithm suitable for real-time content-based multimedia streaming systems is proposed in this paper. A Motion Vector (MV) based object extraction is used to dynamically detect the objects. To utilize the bandwidth efficiently, the important object can be real time detected, encoded, and transmitted with higher quality and higher frame rate than those of background. In order to meet the real-time requirement, no computationally intensive operation is included in this framework. Moreover, in order to guarantee the highest speed, all the implementation is operating on the compressed domain without need for decompression. Good extraction performance is demonstrated by the experiment results.